Efecto de sustratos orgánicos en el desarrollo fisiológico de esquejes de café (Coffea canephora P.) - Salinas-Ruiz, Josafhat; Ortiz-Cervantes, Elías; Hernández-Lara, Mariso; Aguas-Atlahua, Aristarco; Velasco-Velasco, Joel (Ecosistemas y Recursos Agropecuarios, 2021)
The effect of three substrates made from vermicompost and one based on compost was evaluated on the development of physiological variables of cuttings from three coffee clones: INIFAP 00-28, INIFAP 00-24, and INIFAP 97-14 of robusta coffee (Coffea canephora P.) and their interactions. Twelve treatments were studied, arranged in a strip plot block design with factorial structure in the treatments (substrate x clone) with four repetitions; ANOVA and Tukey’s mean comparison (p ≤ 0.05) was performed. In the substrate, the variables pH, electrical conductivity (EC), organic matter (OM), apparent density (Bd), cation exchange capacity (CEC), macro and micronutrients were evaluated; while in the coffee cuttings clones, mortality percentage (M), axillary bud yield percentage (S), rooting percentage (R), outbreak length (OI), number of internodes (Ni), number of leaves (NI), number of roots (Nr) and root length (RI). In the INIFAP substrate, the different types of robusta coffee clones showed the highest physiological development. Among types of clones, clone INIFAP 00-28 presented the highest physiological development of the photosynthesis part (axillary bud yield, outbreak length, number of internodes, number of leaves); however, it showed the least root development. The lowest development was observed in the clone INIFAP 97-14, and the highest root development was observed in the clone INIFAP 00-24 (percentage of rooting, number of roots and root length) while the clone INIFAP 00-28 showed the highest development of the photosynthesis part.